GrpE Immunization Protects Against Ureaplasma urealyticum Infection in BALB/C Mice - Tang, Yanhong; Guo, Fangyi; Lei, Aihua; Xiang, Jing; Liu, Pengqin; Ten, Wenyou; Dai, Guozhi; Li, Ranhui (Frontiers in Immunology, 2020)
Nucleotide exchange factor (GrpE), a highly conserved antigen, is rapidly expressed and upregulated when Ureaplasma urealyticum infects a host, which could act as a candidative vaccine if it can induce an anti-U. urealyticum immune reaction. Here, we evaluated the vaccine potential of recombinant GrpE protein adjuvanted by Freund's adjuvant (FA), to protect against U. urealyticum genital tract infection in a mouse model. After booster immunization in mice with FA, the GrpE can induced both humoral and cellular immune response after intramuscular injection into BALB/c mice. A strong humoral immune response was detected in the GrpE-immunized mice characterized by production of high titers of antigen-specific serum IgG (IgG1, IgG2a, and IgG3) antibodies. At the same time, the GrpE also induced a Th1-biased cytokine spectrum with high levels of IFN-γ and TNF-α after re-stimulation with immunogen GrpE in vitro, suggesting that GrpE could trigger the Th1 response when used for vaccination in the presence of FA. Although GrpE vaccination in the presence of a Th1-type adjuvant-induced had readily detectable Th1 responses, there wasn't increase inflammation in response to the infection. More importantly, the robust immune responses in mice after immunization with GrpE showed a significantly reduced U. urealyticum burden in cervical tissues. Histopathological analysis confirmed that tissues of GrpE-immunized BALB/c mice were protected against the pathological effects of U. urealyticum infection. In conclusion, this study preliminarily reveals GrpE protein as a promising new candidate vaccine for preventing U. urealyticum reproductive tract infection.